President's Message - Socha, Linda (Operating Room Nurses Association of Canada Journal, 2008)
I am writing this message in my hotel room in Ottawa where I am attending the Canadian Nurses Association (CNA) Biennium. ORNAC, as an associate specialty group, attends a networking meeting for the associate/affiliate/emerging groups (AAE) at these biennial conferences. With individuals representing 40 groups you can imagine the energy and the passion!